Розробка новинного it-блогу - Щеглов, І. О. (ХНУРЕ, 2023)
To stay current with the technological advancements, starting a blog is a great idea. But, to win over an audience, one must have a distinct brand identity and voice that adds value to their lives. Promoting the blog using digital marketing tools and social media platforms will extend its reach. To build a loyal readership, publishing new content consistently is integral. Monetization strategies must be conducted with transparency and ethicality to produce income, although engaging with readers can build a robust sense of togetherness. Pairing with other bloggers or prominent figures within an industry can bring a plethora of new viewpoints to the blog